Mutational Analysis of The Er-Exit Code in The C-Terminal Domain of Kir6.2 - Vimala Devi Manickam; Sugapriya Menaga Perumal; Bharathiraja Chinnathambi; Kannan Soundarapandian (Tropical Life Sciences Research, 2009)
Mutations in the gene encoding the potassium channel subunit Kir6.2 can cause congenital hyperinsulinism (CHI). CHI mutations severely affect channel function and trafficking in the ?-cell membrane. The present study reports a novel mutation, E282K, in the Kir6.2 subunit in a patient diagnosed with CHI. The impact of this mutation on channel trafficking is assessed by immunocytochemical studies, and channel function is determined by site-directed mutagenesis. Heterologous expression of Kir6.2 clearly showed that mutations in the DXE code cause the channel to be retained in the ER. Further mutagenic studies revealed that E282K could be a part of the DXE exit code. This raised the possibility that KATP channels may assemble with Sec 23/Sec 24 proteins and exit the ER in COPII vesicles in a process that requires a dominant negative form of Sar1- GTPase (one that was unable to hydrolyse GTP) and prevented the ER exit of wild-type channels. This is due to the mutation in the C-terminal region which prevented the ER exit code. In conclusion, KATP channels use the DXE motif to export newly synthesized proteins from the ER. The functional importance of this code is demonstrated by the severity of CHI, which appears to be due to a genetic mutation in the DXE motif. Thus, the present study provides novel information that Kir6.2 is synthesized in the ER and exported with the aid of the DXE motif in its C-terminal region. Mutasi pada gen yang mengekod subunit Kir6.2 pada saluran potassium, boleh mengakibatkan congenital hyperinsulinism (CHI). Mutasi pada CIH boleh memberi kesan yang teruk terhadap fungsi saluran dan proses keluar masuk dalam membran cel-?. Kajian ini melaporkan suatu mutasi baru E282K, dalam subunit Kir6.2 dalam seorang pesakit yang menghidapi CHI. Impak mutasi ini pada proses keluar masuk saluran dinilai melalui kajian immunositokimia dan fungsi saluran ditentukan oleh mutagenesis site-directed. Pengekspresan heterologous Kir6.2 dengan jelasnya menunjukkan bahawa mutasi di kod DXE telah mengakibatkan saluran kekal dalam ER. Kajian mutagenik yang selanjutnya telah menunjukkan bahawa E282K mungkin termasuk dalam kod exit DXE. Ini telah menyebabkan kemungkinan saluran KATP mungkin berkumpul bersama protin Sec 23/Sec 24, dan keluar dari ER dalam vesikel COPII, dalam satu proses yang memerlukan suatu bentuk Sar1-GTPase yang dominan negatif (iaitu tidak boleh menghidrolisasi GTP), dan menghalang saluran yang jenis liar keluar dari ER. Sebagai kesimpulan, saluran KATP menggunakan motif DXE untuk mengeksport protein-protein yang baru disintesis dari ER. Kepentingan fungsi kod ini didemonstrasikan oleh keterukan CHI, yang kelihatan seperti berpunca daripada mutasi gen di motif DXE. Maka, kajian ini telah menyediakan informasi baru iaitu Kir6.2 telah disintesis dalam ER, dan dieksport dengan bantuan motif DXE di dalam kawasan C-terminalnya.